2000
DOI: 10.1063/1.373475
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and structural properties of polycrystalline silicon

Abstract: This work links the structural and electrical properties of thin polycrystalline silicon films at the level of individual grains. A four point “transparent probe” technique was developed which allowed a small number of grains to be isolated and measured electrically in test structures which can be nondestructively prepared for direct imaging in a transmission electron microscope (TEM). By measuring the temperature dependence of electrical resistance in many test structures, the distribution of individual grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…It has also been reported that individual GBs have different structural and electrical properties. 5,6 Thus control of the electrical properties of GBs is vital for nanometerscale devices, in which only a few grains and GBs may exist in the active region.In this letter we discuss the effect of oxidation and thermal annealing on the electrical and structural properties of poly-Si thin films and on nanowires fabricated in these films. We observe that the film electrical conductivity ͑ ͒ decreases nonmonotonically with an increase in oxidation temperature and that a two-stage oxidation process, followed by annealing, reduces variation in the activation energy of the conductivity (E a ) and tunnel resistance (R T ) in nanowire devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that individual GBs have different structural and electrical properties. 5,6 Thus control of the electrical properties of GBs is vital for nanometerscale devices, in which only a few grains and GBs may exist in the active region.In this letter we discuss the effect of oxidation and thermal annealing on the electrical and structural properties of poly-Si thin films and on nanowires fabricated in these films. We observe that the film electrical conductivity ͑ ͒ decreases nonmonotonically with an increase in oxidation temperature and that a two-stage oxidation process, followed by annealing, reduces variation in the activation energy of the conductivity (E a ) and tunnel resistance (R T ) in nanowire devices.…”
mentioning
confidence: 99%
“…It has also been reported that individual GBs have different structural and electrical properties. 5,6 Thus control of the electrical properties of GBs is vital for nanometerscale devices, in which only a few grains and GBs may exist in the active region.…”
mentioning
confidence: 99%
“…GB's observed in poly-Si are roughly classified into a twin boundary and a random GB. Experimental results showed that twin boundaries were electrically inactive, 4) and it is thought that twin boundaries do not affect the electrical property of poly-Si. In contrast, random GB's are thought to deteriorate the electrical and mechanical properties of poly-Si, since dangling-bonds are possibly formed at these boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the transport properties of these heterogeneous materials are affected significantly by local microstructures. Thus carrier transport has been investigated in localized regions using an AFM/STM [4] and by fabricating wires ranging 0.1 µm -4 µm in width [5]. In this paper, we report the fabrication of very thin nc-Si:H films and their characterization using 30-nm-wide nanowires to investigate the local carrier transport properties.…”
Section: Introductionmentioning
confidence: 99%